Clinical and epidemiological characteristics of import cases of malaria according to the materials of ZRIH 2000-2017 - Vadigala, Balakrishna Reddy; Onishchenko, T.; Оніщенко, Тетяна Євгенівна (Запорізький державний медичний університет, 2018)
After an unprecedented global success in the fight against malaria, progress has slowed down. WHO estimates that the number of malaria cases in 2016 is 5 million higher than in 2015. The number of deaths from malaria remained at 445,000, which is comparable to the 2015 indicator (WHO, 2017). Currently, about half of the world's population is at risk for malaria – 3,2 billion (WHO, 2016). In connection with the increase in migration processes in the world (peacekeeping contingents, tourism, business trips), the problem of malaria is also relevant for non-endemic countries (Golubovskaya OA, 2016, Trikhleb VI 2015). The lack of specific immunization of malaria, cautiousness when visiting endemic regions and chemoprophylaxis are risk factors for severe and complicated malaria. The purpose of the study was to study the clinical and epidemiological features of imported cases of malaria according to the ZRIH. Under supervision in ZRIH from 2000 to 2017 there were 27 patients diagnosed with malaria.
Keywords: тези доповідей